What can we say about the function f : R + → R which satisfies
f ( x y ) = f ( x ) + f ( y ) ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Nice way of proving that it is not a continuous function, because the values of g (but not f ) are rational.
Please prove the details too Sir
Log in to reply
Ok here are some details... feel free to ask for more.
I will freely use basic concepts of linear algebra.
According to the axiom of choice, the vector space R has a basis B over Q . We can define a linear transformation g : R → R by setting g ( r 1 b 1 + . . . . + r n b n ) = r 1 + . . . + r n where the r j are rational and the b j are in B . Note that g ( x + y ) = g ( x ) + g ( y ) by definition.
Then f = g ∘ ln is a function with the required property that f ( x y ) = f ( x ) + f ( y ) . Also, f is discontinuous since its range is Q (the intermediate value theorem does not hold). Any rational number r is in the range since f ( e r b ) = g ( r b ) = r for any basis element b .
Yes sir pls explain in detail
Problem Loading...
Note Loading...
Set Loading...
Interesting, thought-provoking problem! Thanks, @Calvin Lin
Considering a basis of R as a vector space over Q , we can prove the existence of a discontinuous linear transformation g : R → R , using basic concepts of linear algebra.
According to the axiom of choice, the vector space R has a basis B over Q . We can define a linear transformation g : R → R by setting g ( r 1 b 1 + . . . . + r n b n ) = r 1 + . . . + r n where the r j are rational and the b j are in B . Note that g ( x + y ) = g ( x ) + g ( y ) by definition.
Then f = g ∘ ln is a function with the required property that f ( x y ) = f ( x ) + f ( y ) . Also, f is discontinuous since its range is Q (the intermediate value theorem does not hold). Any rational number r is in the range since f ( e r b ) = g ( r b ) = r for any basis element b .